Analysis Structure and Rule Language Text Explanation Magazine Voice Muhammadiyah 19th Edition 2023 - Ananda Aulya Natasya; Syahruddin Syahruddin; Anin Asnidar (Edumaspul: Jurnal Pendidikan, 2024)
The aim of this research is to analyze the structure and linguistic rules of explanatory texts in Suara Muhammadiyah magazine, edition 19 of 2023. This research uses a library research type of research with a . The researcher chose this magazine as research material because it is media produced by Muhammadiyah and there has been no previous research using Suara Muhammadiyah magazine. The results of this research found that in the 19th edition of Suara Muhammdiyah magazine three explanatory texts were found which were composed of a complete structure, namely identification of phenomena, series of incidents, and interpretation. As well as linguistic rules in the form of the use of time adverbial indicators, manner adverbial indicators, causality conjunctions, and pronouns.